3D cellular metamaterials with planar anti-chiral topology. (5th May 2018) - Ebrahimi, Hamid; Mousanezhad, Davood; Nayeb-Hashemi, Hamid; Norato, Julian; Vaziri, Ashkan
Abstract: We constructed a new class of three-dimensional cellular metamaterials by connecting planar structure with anti-chiral topology. This was achieved by introducing a unique node design for connecting planar materials to enable constructing a three-dimensional architecture. This node design is based on linking the circular elements of the anti-chiral topology using oblique load-bearing ligaments. As the planar structure is subjected to loading, the circular elements rotate and the ligaments undergo bending, resulting in out-of-plane deformation of the three-dimensional cellular metamaterials. The node design, and specifically the ligaments' revolution angle govern the behavior of cellular metamaterials. This was demonstrated by designing cellular metamaterials with a wide range of positive and negative Poisson's ratio in the out-of-plane direction. Graphical abstract: Unlabelled Image Highlights: A new class of 3D cellular metamaterials introduced with tunable Poisson's ratio. Wide range of Poisson's ratios, both positive and negative values, is achievable. The behavior of the structure is governed by three geometrical parameters. The design concept provides a framework to develop auxetic cellular materials.